Synchronous Intersection Management to reduce Time Loss - Reddy, Radha (2021)
Conventional intersection management that allows multiple vehicles from one road at a time, e.g., Round-Robin (RR), may constitute bottlenecks in urban traffic management. Consequently, new intelligent intersection management (IIM) approaches were proposed to reduce time loss, fuel wastage, and ecological damage. IIM is also suited to take advantage of the new communication capabilities of autonomous vehicles that are gaining relevance, though still co-existing with human-driven vehicles. This paper extends the analysis of a recently proposed synchronous IIM system, the Synchronous Intersection Management Protocol (SIMP), that is compared with the RR scheme in a four-way single-lane intersection as those found in urban residential areas, under maximum vehicle speeds of 30Km/h and 50Km/h and various traffic arrival rates. We characterize performance by measuring time loss, i.e., the additional trip delay due to forced slowdown, and fuel consumption using a model for standard vehicles with internal combustion engines. The experimental results obtained with the SUMO simulation framework indicate an advantage for SIMP in both metrics, approximately halving the values achieved with the best RR approaches and with high traffic rates.